2004
DOI: 10.1177/1078087403260787
|View full text |Cite
|
Sign up to set email alerts
|

Suburbanization, the Vote, and Changes in Federal and Provincial Political Representation and Influence Between Inner Cities and Suburbs in Large Canadian Urban Regions, 1945-1999

Abstract: This article examines the degree to which the relative growth of suburban electoral districts in Canada’s largest urban regions (Toronto, Montreal, and Vancouver) has lead to a loss of potential political influence within government on behalf of Canadian inner cities and/or to more support for right-wing political parties. The study finds that although inner cities and suburbs have increasingly diverged in their voting behavior in both federal and provincial elections, the growth of suburban electoral district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
(21 reference statements)
3
29
0
Order By: Relevance
“…A deeply neoliberal Conservative (officially 'Progressive Conservative' -PC) government was elected at the provincial level under the premiership of Mike Harris, rapidly implementing a 30% income tax reduction, and a massive roll-back of the welfare state (including cuts to welfare benefits, public sector lay-offs and service cuts), as well as attacks on unions and the restructuring of local governance that would result in amalgamation of the city (for a discussion of the history of political and policy change in Toronto and the province of Ontario over this time, see Boudreau 2000;Boudreau, Keil, and Young 2009;Donald 2002b;Filion and Kramer 2011;Keil 2000Keil , 2002Kipfer and Keil 2002). While the political preferences of voters living in the postwar Fordist suburbs had been diverging from those in the inner cities since the mid-1970s, the political gulf now widened to the point that the PCs could rely solely on the suburbs (both inner and outer) for their victory, with very little support within the old city, who were far more likely to vote for parties of the center and left (Walks 2004). Indeed, the amalgamation of the city by the conservatives was partly meant to dilute the power of left-leaning inner-city councillors, who received their support from the prewar inner city, and to promote the power of right-leaning politicians who received their support from the (inner) suburbs who now constituted the majority (Keil 2000;Sancton 2000).…”
Section: From Permeable Fordisms To Neoliberal Politics: the Toronto mentioning
confidence: 97%
See 1 more Smart Citation
“…A deeply neoliberal Conservative (officially 'Progressive Conservative' -PC) government was elected at the provincial level under the premiership of Mike Harris, rapidly implementing a 30% income tax reduction, and a massive roll-back of the welfare state (including cuts to welfare benefits, public sector lay-offs and service cuts), as well as attacks on unions and the restructuring of local governance that would result in amalgamation of the city (for a discussion of the history of political and policy change in Toronto and the province of Ontario over this time, see Boudreau 2000;Boudreau, Keil, and Young 2009;Donald 2002b;Filion and Kramer 2011;Keil 2000Keil , 2002Kipfer and Keil 2002). While the political preferences of voters living in the postwar Fordist suburbs had been diverging from those in the inner cities since the mid-1970s, the political gulf now widened to the point that the PCs could rely solely on the suburbs (both inner and outer) for their victory, with very little support within the old city, who were far more likely to vote for parties of the center and left (Walks 2004). Indeed, the amalgamation of the city by the conservatives was partly meant to dilute the power of left-leaning inner-city councillors, who received their support from the prewar inner city, and to promote the power of right-leaning politicians who received their support from the (inner) suburbs who now constituted the majority (Keil 2000;Sancton 2000).…”
Section: From Permeable Fordisms To Neoliberal Politics: the Toronto mentioning
confidence: 97%
“…Neoliberalism has been theorized as the ideological accompaniment of the post-Fordist restructuring of the economy toward a globalized cosmopolitan financialized capitalism, and as a remedy for the rigidities and sagging profitability of Fordism (Harvey 2005). Suburban populations are conceptually expected to support neoliberal policies out of a desire to avoid responsibility for funding social programs, welfare-state income redistribution, and/or public infrastructure in the cities (Walks 2004). However, Ford's support in Toronto derives not from post-Fordist exurbia, nor from the gentrified and financialized new inner city, but from the quintessential Fordist (inner) postwar suburbs that furthermore cannot secede from the city, being a part (and indeed the political majority) of the central-city government.…”
Section: Introduction: New Fordism In Toronto?mentioning
confidence: 99%
“…Keil (1998, p. 155) has suggested that the amalgamation of Metropolitan Toronto can be interpreted to a great extent "as a territorial fight between the suburban power bases of [Ontario Premier] Mike Harris and the social democratic and liberal dominance of the inner city" (see also Walks, 2004 for recent empirical evidence on diverging values between the suburbs and the inner city in Canada). Many believe that the amalgamation was a neo-conservative conspiracy to punish and destroy a leftist-oriented social base in the old city of Toronto that had dominated municipal politics at least since the 1970s.…”
Section: Territorial Restructuring Resistance and Response Under Thementioning
confidence: 96%
“…Public opinion research suggests that multiple individual-level factors, particularly race, gender, and class, influence political opinions and policy preferences, particularly in relation to the choice to share resources with people and places deemed different in some way (e.g., Gilens, 1995). Additionally, where people live shapes their political attitudes and guides their behavior (e.g., Huckfeldt, 1986;Huckfeldt, Plutzer, & Sprague, 1993), which is true of the attitudes and behaviors of residents of metropolitan areas (Gainsborough, 2001;Walks, 2004aWalks, , 2004b. Accordingly, turning our attention to the values and preferences of metropolitan residents, we should expect both individual and contextual effects to shape the political orientations of the citizenry of city-regions.…”
Section: The Regional Perspective As a Political Orientation Of Citizmentioning
confidence: 99%